New patient-reported experience measure for children with allergic disease: development, validation and results from integrated care. Issue 10 (2nd August 2016) - Gore, C; Griffin, R; Rothenberg, T; Tallett, A; Hopwood, B; Sizmur, S; O'Keeffe, C; Warner, J O
Abstract : Objectives: To develop and validate a new allergy-specific patient-reported experience measure (PREM) for children and their parents, and to collect feedback in an integrated care setting. Design: Two allergy-specific PREMs were produced using focus groups, cognitive testing, two prospective validation studies (collaboration: Royal College of Paediatrics and Child Health, Picker Institute Europe, Imperial College/London): 'Your Allergy Care', for children aged 8–16 years; 'Your Child's Allergy Care', for parents of children aged 0–7 years. Setting: Community event, primary/secondary/tertiary allergy care settings. Main outcome measures: Performance of PREMs in validation study; reported experience of allergy care. Participants: 687 children with allergic conditions and their parents/carers. Results: In total, 687 questionnaires were completed; 503/687 (253 child; 250 parent) for the final survey. In both surveys, demographic variations were not associated with differences in results. Although 71% of patients reported one or more allergic conditions (food allergy/eczema/hay fever/asthma), 62% required multiple visits before receiving final diagnosis. Overall, patient experience was good for communication with patient/parent, competence and confidence in ability, and 73% felt looked after 'very well' and 23% 'quite well'. Areas for improvement included communication with nurseries/schools, more information on side effects, allergic conditions and allergen/irritant avoidance. Allergy care in primary/emergency care settings was associated with higher problem-scores (worse experience) than in specialist clinics. Conclusions: These new PREMs will allow allergy-specific patient experience reporting for children and parents and help identification of priority areas for improvement and commissioning of care. Efforts towards better allergy care provision must be targeted at primary and emergency care settings and underpinned by improving communication between healthcare providers and the community.